Contextualizing the Conflict between Amīr Mu‘āwiyah (d. 680 AD) and ‘Alī bin Abī Ṭālib (d. 661 AD): A Historical Reassessment - Malik, Javeed Ahmad (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The historical narrative surrounding the conflict between Amīr Mu‘āwiyah (d. 680 AD) and ‘Alī bin Abī Ṭālib (d. 661 AD) has long been cloaked in controversial debate. The former’s refusal to pledge allegiance to the latter stemmed from his demand for Qiṣāṣ (Retribution) following the assassination of ‘Uthmān bin ‘Affān (d. 656 AD). Believing that Ḥaḍrat ‘Alī’s ascension to the Khilāfah (Caliphate) did not adequately address the grievances, Amīr Mu‘āwiyah withheld his adherence, viewing it as a means to accentuate for Qiṣāṣ. This denial inflamed tensions and fueled the broader dispute between them, underscoring an intense impact on the political landscape of the Muslims in the early decades. Drawing upon a range of sources, while employing critical textual analysis, this paper attempts to offer a broader understanding of the events that occurred during this crucial period with their deeper historical context. Through scrupulous revision of the authentic historical accounts, this study, primarily, aims to scrutinize the growing accusation labeling Amīr Mu‘āwiyah as a rebel owing to his stand against Ḥaḍrat ‘Alī, and seeks to evaluate the validity of such a budding narrative about his intentions. Moreover, it shall endeavor to shed light on Amīr Mu‘āwiyah’s role and motivations, ultimately contributing to a historically exact portrayal of his position. It shall also enrich scholarly discourse and foster a more nuanced understanding of early Muslim history.